Study of electrical behavior of liquid crystal devices doped with titanium dioxide nanoparticles - Marzal, Vicente; Torres, Juan Carlos; García, Braulio; Pérez, Isabel; Sánchez, José Manuel; Piecek, Wiktor (Photonics Letters of Poland, 2017)
In the last years, nanostructures are widely used as dopants in liquid crystals to manipulate either their electrical or optical properties. In this work, we have analyzed the electrical response of a planar cell filled with a mixture of E7 liquid crystal doped with TiO2 nanoparticles. The effect of these dopants on the effective permittivity and conductivity of the cell has been studied in a wide frequency range at different temperatures. Full Text: PDF References P.J. Pinzón, I. Pérez, C. Vázquez and J.M.S. Pena, "Reconfigurable ????×????1×2 wavelength selective switch using high birefringence nematic liquid crystals", App.Opt. 51, pp.5960-5965 (2012) CrossRef C. Carrasco-Vela, X. Quintana, E.Otón, M.A. Geday, J.M. Otón, "Security devices based on liquid crystals doped with a colour dye", Opto?Electron. 19, pp.496-500 (2011). CrossRef J. Torrecilla, E. Ávila-Navarro, C. Marcos, V. Urruchi, J.M.S. Pena, J. Arias, M.M Sánchez-López, "Microwave Tunable Notch Filter Based on Liquid Crystal Using Spiral Spurline Technology", Microw. Opt. Technol. Lett. 55, 2420-2423 (2013). CrossRef G.B. Hadjichristov, Y. G. Marinov, A. G. Petrov, E. Bruno, L.Marino, N. Scaramuzzab, "Electro-Optics of Nematic/Gold Nanoparticles Composites: The Effect from Dopants", Mol. Cryst. Liq. Cryst. 610, 135?148 (2015). CrossRef T. Miyama, J. Thisayukta, H. Shiraki, Y. Sakai, Y. Shiraishi, N. Toshima, S. Kobayashi, "Fast Switching of Frequency Modulation Twisted Nematic Liquid Crystal Display Fabricated by Doping Nanoparticles and Its Mechanism", Jpn. J. Appl. Phys. 43, 2580 -2584 (2004). CrossRef W. T. Chen, P. S. Chen, C. Y. Chao, "Effect of Doped Insulating Nanoparticles on the Electro-Optical Characteristics of Nematic Liquid Crystals", Jpn. J. Appl. Phys. 48, 015006 (2009) CrossRef A. Siarkowska, M. Chychłowski, T.R. Woliński and A.Dybko. "Titanium nanoparticles doping of 5CB infiltrated microstructured optical fibers", Phot. Lett. Poland 8, 29-31 (2016). CrossRef O. Buchnev, A. Dyadyusha,M. Kaczmarek, V.Reshetnyak, Y. Reznikov, "Enhanced two-beam coupling in colloids of ferroelectric nanoparticles in liquid crystals", J. Opt. Soc. Am. 24, 1512-1516 (2004). CrossRef A. García-García, R. Vergaz, J.A. Algorri, X. Quintana, J.M. Otón, Beilstein J. "Electrical response of liquid crystal cells doped with multi-walled carbon nanotubes", Nanotechnol. 6, 396?403 (2015). CrossRef R. Pratibha, K. Park, I.I. Smalyukh and W. Park, "Tunable optical metamaterial based on liquid crystal-gold nanosphere composite", Opt. Express 17,19459-19469 (2009). CrossRef J.C. Torres, B. Garcia-Camara, I. Perez, V. Urruchi, J.M. Sanchez-Pena, "Temperature-Phase Converter Based on a LC Cell as a Variable Capacitance", Sensors 15, 5594 ? 5608 (2015). CrossRef P. Kumar, A. Kishore and A, Sinha, "Effect of different concentrations of dopant titanium dioxide nanoparticles on electro-optic and dielectric properties of ferroelectric liquid crystal mixture ", Adv. Mater. Lett. 7, 104-110 (2016). CrossRef R.K. Shukla, C.M. Liebig, D.R. Evans, and W. Haase, "Electro-optical behaviour and dielectric dynamics of harvested ferroelectric LiNbO3 nanoparticle-doped ferroelectric liquid crystal nanocolloids", RSC Adv. 4, 18529-18536 (2014). CrossRef